The Implementation Of Icebreaker Technique Toward Students’ Speaking Skill And Their Motivation In Englishlanguage Teaching At Senior High School 1 Gunung Labuhan - Dwi Mahya Sari; Merlyn Kristine Nelloe; Agus Rofií; Rangga Mege Putra; Nining Fitriani; Petrus Yacob Pattiasina (Departement of Mathematics Education, 2023)
The success of English Language Teaching is indicated by the mastery of communicative competence by the students. One of them is sociolinguistic competence that is focused on human interaction. In this research, researcher would to find out what the teachers have done to students’ speaking skill and students’ motivation through Icebreaker technique or in other words to figure out the process and the final result of the learning of speaking. This was descriptive quantitative; The subjects of this research were English teachers at the Junior High School 2 Gunung Labuhan. The data were collected through classroom observation, speaking test, and questionnaire. The results showed that (1) Almost in every meeting the teachers used Icebreaker technique such as guessing word, riddle, sharing experience, burning question, topic lead in, quiz and brainstorming. These were used to motivate and train students to speak up, and also make the students enjoy and active in the process of teaching and learning. (2) Students speaking skill were good; it can be seen from their score for every component, students’ comprehension (4.48), Grammar (4.1), Vocabulary (4.34), Pronunciation (4.18), and fluency (3.88). (3) Icebreaker motivates students to ask and answer teachers’ questions during the process of learning. It also rouses up students’ interest to learn. Based on the finding, the researcher concludes that Icebreaker technique is useful, especially in increasing students speaking skill and also their motivation in teaching and learning process.